2007
DOI: 10.1002/ajmg.a.31605
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of a 26‐year‐old male with duplication of 16p: Clinical report and review

Abstract: We report on a 26-year-old male with profound psychomotor retardation and a pattern of dysmorphic features and malformations characteristic for duplication of the short arm of chromosome 16. He has an elongated face, sparse hair, upslanting palpebral fissures, anteverted nostrils, hypoplastic thumbs on both hands, and dislocation of several joints. His chromosome aberration was diagnosed at birth and was due to an unbalanced segregation of a maternal translocation t(2;16)(q36;p11). At 26 years of age he is, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Nevertheless, in patients with complete trisomy 16p it was not possible to identify a characteristic phenotype similar to that found in cases with duplication of the distal segment. 15 Pre-and postnatal growth and mental retardation were more severe in patients with complete trisomy 16p. A distinctive phenotype different to that identified in our patients has been recently described in a girl with duplication limited to the Rubinstein -Taybi region on 16p13.3, probably representing a single gene disorder.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, in patients with complete trisomy 16p it was not possible to identify a characteristic phenotype similar to that found in cases with duplication of the distal segment. 15 Pre-and postnatal growth and mental retardation were more severe in patients with complete trisomy 16p. A distinctive phenotype different to that identified in our patients has been recently described in a girl with duplication limited to the Rubinstein -Taybi region on 16p13.3, probably representing a single gene disorder.…”
Section: Discussionmentioning
confidence: 97%
“…Several literature reports deal with partial duplication of chromosome 16p13 [Kokalj-Vokac et al, 2000;Martin et al, 2002;de Ravel et al, 2005;Rochat et al, 2007], and a common phenotype is suggested, characterized by severe psychomotor retardation, growth delay with microcephaly, seizures, major malformations, such as cleft palate, congenital heart defects and genitourinary abnormalities, and a specific facial appearance with round head, upslanting and narrow palpebral fissures, sparse eyebrows, broad nasal bridge, rounded nasal tip, prominent glabella, long philtrum, thin upper lip and micrognathia. However these duplications are much larger than the duplication detected in our patient and, in addition, they are usually associated with a complex cytogenetic imbalance, affecting different chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The distinguishing clinical features of dup16p syndrome, determined by the terminal 16p13.1-p13.3 critical region, include specific facial anomalies, mental retardation, congenital cardiac and vascular defects, urinary malformations, and hypoplastic distal phalanges of hands [611]. Our case demonstrated a duplication of the subtelomeric region of chromosome 16p representing a chromosome 16p duplication, encompassing the critical region of 16p13.1-p13.3.…”
Section: Discussionmentioning
confidence: 82%